2022
DOI: 10.1111/ajag.13080
|View full text |Cite
|
Sign up to set email alerts
|

A ‘plethora of services’ but a lack of consistency: A qualitative study of service providers' perspectives about transitioning from hospital to home for older South Australians

Abstract: Objective We explored the perspectives of professionals working in health and aged care services in South Australia about factors that influenced successful transitions from hospital to home or residential aged care home for older people. We examined successful and recommended strategies that could support safe transitions following hospital discharge and reduce avoidable hospital admissions in South Australia. Methods Nineteen professionals from acute, post‐acute, primary, community and aged care settings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…With the COVID-19 pandemic, limited contact between older adults and their families and healthcare providers has facilitated the widespread use of telemedicine ( 61 , 62 ). Despite the fact that older adults are largely digitally illiterate, studies have found that older adults find tele-rehabilitation acceptable, improving access to health care ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the COVID-19 pandemic, limited contact between older adults and their families and healthcare providers has facilitated the widespread use of telemedicine ( 61 , 62 ). Despite the fact that older adults are largely digitally illiterate, studies have found that older adults find tele-rehabilitation acceptable, improving access to health care ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a division of responsibility for hospital, disability, primary and aged care services, and, as a result, there are multiple barriers to the efficient transition of information and patients between them. 14 In the current volume-based model, providers make more money by providing more care, which has created a system that incentivises overtreatment. This issue is widespread and cross-disciplinary, and, unless addressed, will only amplify the ill effects of future challenges to the system.…”
Section: The Challengesmentioning
confidence: 99%
“…Today, the Australian health care system is highly fragmented, with much of it resolutely designed to produce volume rather than value‐based care. There is a division of responsibility for hospital, disability, primary and aged care services, and, as a result, there are multiple barriers to the efficient transition of information and patients between them 14 . In the current volume‐based model, providers make more money by providing more care, which has created a system that incentivises overtreatment.…”
Section: The Challengesmentioning
confidence: 99%